PERSINGGUNGAN TASAWUF DAN HADIS DI NEGERI BAWAH ANGIN PADA ABAD KE-17: Telaah Shurūṭ al-ʻārif al-Muḥaqqiq Karya Syaikh Yusuf al-Makassari - Alhusni, Alhusni; Sulistio, Dody; Kurniawan, Edi (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
Indonesia-Malay scholars in the past have paid great attention to hadith, but a special work which prescribes hadiths with Sufism nuances, Shaykh Yusuf was the initial figure who started it. However, studies on Shaykh Yusuf’s tasawuf thought have so far focused more on tasawuf itself, paying little attention to hadith’s aspects. This article discusses the intersection of Sufism and hadith in Shurūṭ al-ʻĀrif al-Muḥaqqiq by Shaykh Yusuf, a work that elaborate two hadiths: qalb al-mu’min ʻarsh Allāh and man ʻarafa nafsah fahuwa ʻarafa rabbah. This paper shows that from the hadith of qalb al-mu’min ʻarsh Allāh emerged the key terms such as al-qalb, al-insān al-kāmil, al-iḥāṭah, al-maʻiyyah, and conditions al-ʻārif al-muḥaqqiq borrowed from earlier Sufis such as Junayd al-Baghdadi, al-Ghazali, Ibn ʻArabi and others. However, Shaykh Yusuf’s creativity lies in his elaboration of these five key terms as the basis for the intersection of hadith and tasawwuf in the hadith man ʻarafa nafsah fahuwa ʻarafa rabbah i.e. those who know themselves, then realize that they do not exist, all that exists is Being al-Ḥaqq, so that he also proceeds to become a perfect person, al-insān al-kāmil. Para ulama nusantara telah menaruh perhatian besar terhadap hadis, tetapi suatu karya khusus yang mensyarahkan hadis-hadis bernuansa tasawuf, Syaikh Yusuf merupakan tokoh awal yang mengawalinya. Hanya saja, kajian-kajian terhadap pemikiran tasawuf Syaikh Yusuf selama ini lebih difokuskan pada tasawuf itu sendiri, kurang memperhatikan aspek hadis. Tulisan ini mendiskusikan persinggungan tasawuf dan hadis dalam Shurūṭ al-ʻĀrif al-Muḥaqqiq karya Syaikh Yusuf, sebuah karya yang mensyarahkan dua hadis: qalb al-mu’min ʻarsh Allāh dan man ʻarafa nafsah fahuwa ʻarafa rabbah. Tulisan ini merupakan kajian pustaka dimana sumber utamanya dari bahan-bahan kepustakaan. Tulisan ini menyimpulkan bahwa dari hadis qalb al-mu’min ʻarsh Allāh muncullah istilah-istilah kunci seperti al-qalb, al-insān al-kāmil, al-iḥāṭah, al-ma‘iyyah, dan syarat-syarat al-‘ārif al-muḥaqqiq yang ia pinjam dari para sufi terdahulu seperi Junayd al-Baghdadi, al-Ghazali, Ibnu ‘Arabi dan lain-lain. Hanya saja, kreatifitas Syaikh Yusuf terletak pada elaborasinya terhadap kelima istilah kunci tersebut sebagai landasan terhadap persinggungan hadis dan tasawuf pada hadis man ʻarafa nafsah fahuwa ʻarafa rabbah, yakni orang yang kenal akan dirinya, maka sadar bahwa ia tidak ada, yang ada hanyalah Wujud al-Ḥaqq, sehingga ia berproses menuju insan paripurna, al-insān al-kāmil.